New sniffing at New World primates: recent advances in the study of platyrrhine olfactory communication. Issue 3 (4th May 2022) - Heymann, Eckhard W.
Abstract : This paper reviews the advances made in the study of olfactory communication in New World primates (Platyrrhini) made since the last major review in 2006, particularly the findings on scent-marking. Relatively few papers specifically addressed this topic, and some others include pertinent information collected during studies addressing other research questions. The majority of papers stems from research on callitrichids and night monkeys. Results of the latter studies refute my earlier hypothesis on a link between sex-biased scent marking and the relative importance of paternal care, but emphasize the need for using sexual selection as a theoretical framework for analyzing olfactory communication. The only two papers that examined scent marking in the context of territoriality and intergroup relations rejected a territorial function, but this remains a debated issue. I suggest to exploit the quasi-experimental condition created by habitat fragmentation to address this question. Portable Gas Chromatography-Mass Spectrometry (GC-MS) devices have been employed for the first time to examine the chemical composition of scent-gland secretions of wild New World primates. Expanding this technology to examine scent marks in situ and how their chemical profile and thus information content changes after deposition will be a promising approach for the future. Finally, I propose to integrate the theoretical framework developed by Carthey and co-workerson the role of microbes for the mediation of olfactory communication into studies of New World primate scent marking.